Domestic impacts of China's WTO accession. - Wang, Jing. (2008)
The process of China seeking entry into the World Trade Organization which is a multilateral institution governing international trade in goods and services, has been underway over thirteen years. The road towards WTO was somewhat time-consuming in terms of completing most of accession protocols necessary for membership in this trading club. Yet China has already joined the trading regime WTO since 2001. The journey of China's WTO bid is however not an end for its financial integration in the world economy. China has to face both opportunities and threats in post-WTO competition.